Differences in emergency nurse triage between a simulated setting and the real world, post hoc analysis of a cluster randomised trial. Issue 7 (1st July 2022) - Morreel, Stefan; Verhoeven, Veronique; Philips, Hilde; Meysman, Jasmine; Homburg, Ines; De Graeve, Diana; Monsieurs, KG
Abstract : Objectives: In the TRIAGE trial, a cluster randomised trial about diverting emergency department (ED) patients to a general practice cooperative (GPC) using a new extension to the Manchester Triage System, the difference in the proportion of patients assigned to the GPC was striking: 13.3% in the intervention group (patients were encouraged to comply to an ED or GPC assignment, real-world setting) and 24.7% in the control group (the assignment was not communicated, all remained at the ED, simulated setting). In this secondary analysis, we assess the differences in the use of the triage tool between intervention and control group and differences in costs and hospitalisations for patients assigned to the GPC. Setting: ED of a general hospital and the adjacent GPC. Participants: 8038 patients (6294 intervention and 1744 control). Primary and secondary outcome measures proportion of patients with triage parameters (reason for encounter, discriminator and urgency category) leading to an assignment to the ED, proportion of patients for which the computer-generated GPC assignment was overruled, motivations for choosing certain parameters, costs (invoices) and hospitalisations. Results: An additional 3.1% (p<0.01) of the patients in the intervention group were classified as urgent. Discriminators leading to the ED were registered for an additional 16.2% (p<0.01), mainly because of a perceived need for imaging. Nurses equally chose flow charts leading to the ED (p=0.41) and equally overruled the protocol (p=0.91). In the intervention group, the mean cost for patients assigned to the GPC was €23 (p<0.01) lower and less patients with an assignment to the GPC were hospitalised (1.0% vs 1.6%, p<0.01). Conclusion: Nurses used a triage tool more risk averse when it was used to divert patients to primary care as compared with a theoretical assignment to primary care. Outcomes from a simulated setting should not be extrapolated to real patients. Trial registration number: NCT03793972 .